The impact of green investment on the economic growth quality - Ziyu, Shao; Dzeraviaha, Ihar P. (Journal of the Belarusian State University. Economics, 2023)
This paper studies the impact of green investment on the economic growth quality. First of all, in order to measure the economic growth quality, this paper proposes an indicator system based on five dimensions of innovation, coordination, green, openness and sharing, and utilises the entropy weighting method to assign weights. Then, based on panel data for 30 Chinese provinces from 2010 to 2020, a two-way fixed effects model is used to empirically examine the impact of green investment on the economic growth quality. The results show that while keeping other conditions unchanged, an increase of 1 trln yuan in green investment can increase the quality index of economic growth by 0.3 units, which is 1.6 times the current average value of the index in China. Moreover, this positive effect has a certain lag. These conclusions remain valid on the basis of taking into account the endogeneity issue and a series of robustness checks. Finally, with a view to effectively improving the economic growth quality, appropriate measures of economic policy are proposed.